The influence of leadership style, job promotion, and communication on employee performance at PT. Indonesia Asahan Aluminium (INALUM), Kuala Tanjung, North Sumatra - Doni Hamdani; Andre Fitriano; Ledi Agustin Hutagalung; M. Nelson Pinem (Journal of Economics and Business Letters, 2023)
The aim of this study was to assess the influence of Leadership on the performance of employees at PT Inalum Kuala Tanjung, to understand the effect of Job Promotion on employee performance, and to examine the impact of Communication on employee performance. It also sought to simultaneously determine the effects of Leadership, Job Promotion, and Communication on the performance of the PT Inalum Kuala Tanjung staff. The study was conducted at PT Inalum Kuala Tanjung, with a population of 100 people who all participated as the research sample. This quantitative descriptive research utilized a questionnaire instrument, data analysis techniques for validity and reliability testing, classic assumption tests, and multiple linear regression. The t-test (partial), F-test (simultaneous), and coefficient of determination were also employed. The result of the multiple linear regression equation revealed significant impacts of Leadership, Job Promotion, and Communication on employee performance, which was confirmed through individual (t-tests) and simultaneous (F-tests) statistical significance. The Leadership, Job Promotion, and Communication variables all showed higher t-test values than the tabulated t-values, and lower significance values than the benchmark 0.05. The F-test value for the combined effect of Leadership, Job Promotion, and Communication was also found to be higher than the tabulated F-value, and its significance value was lower than 0.05. In conclusion, Leadership significantly influences performance, Job Promotion significantly affects employee performance, and Communication significantly impacts employee performance. Simultaneously, Leadership, Job Promotion, and Communication have a significant influence on employee performance at PT Inalum Kuala Tanjung.